2014
DOI: 10.1128/cvi.00482-14
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Mycelial Catalase from Scedosporium boydii, a Useful Tool for Specific Antibody Detection in Patients with Cystic Fibrosis

Abstract: bScedosporium boydii is an opportunistic filamentous fungus which may be responsible for a wide variety of infections in immunocompetent and immunocompromised individuals. This fungus belongs to the Scedosporium apiospermum species complex, which usually ranks second among the filamentous fungi colonizing the airways of patients with cystic fibrosis (CF) and may lead to allergic bronchopulmonary mycoses, sensitization, or respiratory infections. Upon microbial infection, host phagocytic cells release reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…This protein sequence revealed the presence of six potential N-glycosylation sites and eleven O-glycosylated sites which confirms the presence of glycosylated residues demonstrated previously on the purified enzyme by affinity chromatography and Western-blotting (Mina et al 2015). The N-terminal region of S. boydii catalase A1 comprised a 26 amino acid-motif corresponding to a signal peptide responsible for the membrane translocation of the protein and its secretion into the culture medium, which is in agreement with detection of the enzyme in culture supernatants (Mina et al 2015).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This protein sequence revealed the presence of six potential N-glycosylation sites and eleven O-glycosylated sites which confirms the presence of glycosylated residues demonstrated previously on the purified enzyme by affinity chromatography and Western-blotting (Mina et al 2015). The N-terminal region of S. boydii catalase A1 comprised a 26 amino acid-motif corresponding to a signal peptide responsible for the membrane translocation of the protein and its secretion into the culture medium, which is in agreement with detection of the enzyme in culture supernatants (Mina et al 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Analysis of deduced protein sequences suggests that there are enough epitope differences between S. boydii catalase A1 and its ortholog in A. fumigatus. Indeed, our previous study showed that a specific serological test for scedosporiosis could be developed using biochemically purified S. boydii catalase A1 (Mina et al 2015). Moreover, anti-Lomentospora prolificans catalase immunoglobulins A were detected in the saliva from healthy immunocompetent individuals .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations